PENERAPAN MEDIA CANVA POSTER TERHADAP HASIL BELAJAR KELAS XI IPS SMA NEGERI 5 PONTIANAK - Koesnadi, Faysal; Asriati, Nuraini; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this study is to determine the impact of canva-poster media on the results of the economics coursework completed by students in grades XI and IPS at SMA Negeri 5 Pontianak. Penelitian using a quantitative sampling technique combined with the qualitative experimental research methodology. Around 60 people participated in this study's data collection, and they were divided into two groups: kelas eskperimen (for creating canva-posters) and kelas kontrol (for comparison). sumber data penelitian di SMA Negeri 5 Pontianak, kelas XI IPS 1 dan 2 as eksperimen mata pelajaran ekonomi, diambil dari data dengan nilai terendah as kelas eksperimen. Data collection methods involving classroom observation, as well as pretest and posttest testing. Variables with the word "media" in them include "canva-poster" (X) and "terikat hasil belajar peserta didik" (Y). The results of the t test hypothesis testing in this study showed that there was planning and implementation and significant positive learning outcomes in the application of Canva-poster media to student learning outcomes. There were differences in the average student learning outcomes from the comparison of pretest and posttest scores. Based on the output, t was obtained. -count is 2.548 and t-table (0.05/2;df) is 2.048. In this case, thiting = 2.548 ttable = 2.048 results in Ho being rejected and Hi being recited as evidence that there is similarity between the two sample groups. Thus, there are distinguishable results from the use of cavna-poster medium compared to the results of the economics course taken by students in the fifth grade at SMA Negeri in Pontianak.